Canopy vs. soil effects of shrubs facilitating tree seedlings in Mediterranean montane ecosystems - Gómez-Aparicio, LORENA; Gómez, Jose M.; Zamora, Regino; Boettinger, Janis L. (Journal of Vegetation Science, 2005)
Abstract. Question: Is the facilitative effect of nurse shrubs on early recruitment of trees mediated by a ‘canopy effect’(microclimate amelioration and protection from herbivores), a ‘soil effect’(modification of soil properties), or both? Location: Two successional montane shrublands at the Sierra Nevada Protected Area, SE Spain. Method: Seedlings of Quercus and Pinus species were planted in four experimental treatments: (1) under shrubs; (2) in open interspaces without vegetation; (3) under shrubs where the canopies were removed; (4) in open interspaces but covering seedlings with branches, mimicking a shrub canopy. Results: Both effects benefited seedling performance. However, microclimatic amelioration due to canopy shading had the strongest effect, which was particularly pronounced in the drier site. Below-ground, shrubs did not modify soil physical characteristics, organic matter, total N and P, or water content, but significantly increased available K, which has been shown to improve seedling water-use efficiency under drought conditions. Conclusions: We propose that in Mediterranean montane ecosystems, characterised by a severe summer drought, pioneer shrubs represent a major safe site for tree early recruitment during secondary succession, improving seedling survival during summer by the modification of both the above-and below-ground environment.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Nurse shrub; Positive interaction; Potassium; Removal experiment; shade